A medical device containing purified bovine colostrum (Monurelle Biogel) in the treatment of vulvovaginal atrophy in postmenopausal women: Retrospective analysis of urinary symptoms, sexual function, and quality of life. Issue 2 (23rd October 2017) - Schiavi, M. C.; Di Tucci, C.; Colagiovanni, V.; Faiano, P.; Giannini, A.; D'Oria, O.; Prata, G.; Perniola, G.; Monti, M.; Zullo, M. A.; Muzii, L.; Benedetti Panici, P.
Abstract : Objective: This study assessed the effectiveness and safety of a medical device containing purified bovine colostrum (Monurelle Biogel; Zambon, Bresso, Italy) in improving vulvovaginal atrophy (VVA), sexual function, urinary symptoms, and quality of life (QoL) in postmenopausal women. Methods: In all, 172 postmenopausal women with VVA were included in the study. All women were treated with vaginal Monurelle Biogel daily for 12 weeks. Patients underwent clinical examinations, completed a 3‐day voiding diary, and had VVA graded using the Vaginal Health Index (VHI) at baseline and 12 weeks. Patients also completed the Female Sexual Function Index (FSFI), overactive bladder questionnaire (OAB‐Q), and the Urogenital Distress Inventory (UDI‐6), among others. Results: After 12 weeks, there were significant increases in mean (± SD) VHI (12.53 ± 3.67 vs. 19.31 ± 3.49; P  < .0001), the number of patients engaging in regular sexual activity 102 (59.3%) vs. 144 (83.7%), and in the total FSFI score (21.64 ± 2.99 vs. 28.16 ± 1.93; P  < .0001) compared with baseline. In addition, there were significant reductions in the mean number of 24‐hour voids (9.57 ± 2.12 vs. 7.13 ± 1.22; P  < .0001), urgent micturition episodes per 24 hours (1.75 ± 0.76 vs. 1.14 ± 0.87; P  = .001), nocturia episodes (1.58 ± 0.85 vs. 0.97 ± 1.18; P  = .0002), and urinary incontinence episodes per 24 hours (0.74 ± 0.59 vs. 0.28 ± 0.52; P  = .003). Finally, after 12 weeks treatment, there were significant differences in UDI‐6 (7.85 ± 0.81 vs. 5.56 ± 1.40), OAB‐Q symptom (53.60 ± 12.57 vs. 22.08 ± 9.63), and OAB‐Q health‐related QoL (21.75 ± 8.51 vs. 69.34 ± 14.59) scores compared with baseline ( P  < .0001 for all). The Patient Impression of Global Improvement scale revealed global improvement in 143 women (83.14%). Conclusions: Monurelle Biogel is an effective treatment for VVA in postmenopausal women, improving sexual life, urinary symptoms, and QoL.